2020
DOI: 10.21608/ejabf.2020.67580
|View full text |Cite
|
Sign up to set email alerts
|

Industrial wastewater remediation using Hematite@Chitosan nanocomposite

Abstract: The emission of heavy metals into the environment may be natural or anthropogenic (Taghipour and Mosaferi, 2013). Anthropogenic impacts including industrial discharge, domestic sewage, non-point source runoff and atmospheric precipitation are the main sources of toxic heavy metals that enter aquatic systems ﴾Langston et al., 1999﴿. Heavy metals are bio-accumulated in living organisms when taken up and stored more than softened (metabolized) or excreted (Gupta, 2013). Heavy metals toxicity has been reportable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The characteristic peak near 895 cm −1 , indicating the presence of metal‐C vibration bond. The above information confirmed the formation of MnSb 2 O 6 ‐chitosan nanocomposites …”
Section: Results and Desiccationsupporting
confidence: 72%
See 1 more Smart Citation
“…The characteristic peak near 895 cm −1 , indicating the presence of metal‐C vibration bond. The above information confirmed the formation of MnSb 2 O 6 ‐chitosan nanocomposites …”
Section: Results and Desiccationsupporting
confidence: 72%
“…Figure B showed XRD patterns of MnSb 2 O 6 ‐chitosan nanocomposites. The nanocomposite has amorphous nature, and the strong characteristic diffraction peaks at 2θ = 27.69°, 35.21°, and 54.03° revealed that the MnSb 2 O 6 nanoparticles were successfully coated by amorphous chitosan “with peaks between 2θ of 10° and 15° with an amorphous structure of chitosan” …”
Section: Results and Desiccationmentioning
confidence: 99%
“…The as‐synthesized Fe 2 O 3 nanoparticles showed the average particle size of 33.5 nm. Dgoodbreak=0.940.25emλβ0.25emcosθ Surface morphology is an important parameter for adsorption capacity of heavy metal ions such as Pb(II), Cd(II) and Cu(II). [ 31,40,42–44 ] Figure 3 shows the SEM images of Fe 2 O 3 and ChS@Fe 2 O 3 . As seen in Figure 3a, the morphology of Fe 2 O 3 is irregular with well narrow size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 ] As seen in Figure 10, after 5 adsorption–desorption cycles, the maximum of removal Pb(II) and Cd(II) ions remained 88 and 72%, respectively, indicating that the ChS@Fe 2 O 3 is well adsorbent for Pb(II) and could be used repeatedly. [ 43,44,46,49 ]…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an alternative solution is using a layered structure such as clay, which is highly available, and a high‐potential adsorbent . Note that mesoporous silica structures or layered structures alone do not possess the necessary productivity for absorbing heavy metals …”
Section: Introductionmentioning
confidence: 99%